Integrating classical islamic texts and digital technology revitalization of kutub al-turats in ma’had dār al-qur’ān wa al-ḥadīth NW Anjani Lombok - Nasri, Ulyan; Fahrurrozi , Fahrurrozi; Haryadi, Lalu Fauzi; Nasirin , Nasirin; Nurdiah , Nurdiah; Hajras, Multazam; Ramdana, Sohri (Universitas Ahmad Dahlan, 2025)
This study examines the revitalization of kutub al-Turats within the framework of Islamic education at Ma’had Dār al-Qur’ān wa al-Ḥadīth NW Anjani, Lombok, in response to the challenges of the digital era. It explores how the integration of classical Islamic texts with digital tools can strengthen both the spiritual and intellectual development of students. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings indicate that the Ma’had has effectively leveraged digital technology to increase students’ access to and engagement with kutub al-Turats, leading to a deeper understanding of Islamic knowledge and the reinforcement of moral and ethical values. This case demonstrates that a balanced integration of tradition and technology can enhance the relevance of Islamic education without compromising its core principles. Although the study is context-specific and its findings may not be widely generalizable, it provides practical and theoretical insights into how Islamic educational institutions can adapt to the digital age while preserving the richness of classical Islamic heritage.